(3GdJYdjbGJ GdSfjI Ydi GdYbjOI GdhGSWjI (B/s - (3Bd eHGQc, ajUd Hf YHO GdYRjR s 1313-1376 (3gLQjG(B.s; (3GdTGjY, YHO GdEdg Hf YKeGf s 1393 (3gLQj(B-s; (3Hf JjejI, CMeO Hf YHO GdMdje Hf YHO GdSdGes 661-728 (3g`(B.s ((3GdQjGV (B:s (3OGQ GdUejYj ddfTQ hGdJhRjY,s, 2006)
(3aj GdYbjOI GdESdGejI(B.s
Keywords: (3Yde GdcdGes; (3YbjOIs